Research as a driver of change: a new perspective on social work (a review of Tetyana Semigina’s book "Promoting change: research in social work") - Slozanska, Hanna (Social work and education, 2025)
The first days of 2025 were marked by the publication of Tetyana Semigina's book "Promoting Change: Research in Social Work" (Semigina, 2025). A scientific work has appeared in the domestic professional literature on social work, which includes a comprehensive analysis of research paradigms in social work - positivist, interpretative and critical. At the same time, the overall emphasis in the publication is on the role of research approaches in improving social services and improving the lives of vulnerable groups of the population.